Invasive hydatidiform mole coexistent with normal fetus. Case report - Tipiani Rodríguez, Oswaldo (2020)
We report the case of a pregnant woman referred to our hospital for suspected partial hydatidiform mole. Ultrasound images showed a normal fetus attached to a small placenta adjacent to a honeycomb-like tumor mass. Amniocentesis revealed a normal karyotype. Due to β-hCG values greater than 800 000 IU and a mass growth of 11% by magnetic resonance imaging, an ultrasound-guided percutaneous tumor biopsy was performed; it ruled out the possibility of choriocarcinoma. The patient had symptoms of hyperthyroidism that required treatment; when the β-HCG levels exceeded one million IU, a course of chemotherapy was prescribed. At 29 weeks, the patient started labor; a cesarean hysterectomy was performed, obtaining a live newborn with Apgar 5 and 7. The pathology report informed the placental mass as an invasive mole. According to our literature search, this is the first case report where an invasive mole coexisted with a healthy fetus. We highlight the importance of using all diagnostic and management tools necessary to achieve fetal viability, without increasing the maternal risk of complications.